Mengungkap Akar Terjadinya Korupsi Pada Belanja Pemerintah Daerah Di Provinsi Sulawesi Tengah - Arief Rahmattullah Tahir; Haryono Pasang Kamase; Muhammad Ansar; Mustamin Mustamin (Politeknik Ganesha Medan, 2026)
This study aims to explore the root causes of corruption in regional government spending in Central Sulawesi Province by highlighting the relationship between electoral politics, bureaucracy, and law enforcement. Although the number of corruption cases decreased from 13 in 2023 to 11 in 2024, the value of state losses increased from IDR 12.5 billion to IDR 39.3 billion. This condition indicates that corrupt practices in the region are increasingly structured and have a significant impact on governance. This study used qualitative methods based on secondary data. The results show that corruption in Central Sulawesi is a systemic process that begins with expensive electoral politics, bureaucratic consolidation through the buying and selling of positions, the exploitation of public projects as a source of rent, the co-option of law enforcement officers as a shield of power, to the practice of extortion, weak oversight, and the emergence of intimidation and impunity. Overall, the findings indicate the formation of a corrupt ecosystem that reproduces itself through the exchange of money, positions, and legal protection. Theoretically, this study broadens understanding of corrupt behavior in the regional bureaucracy, while practically, it provides recommendations for supervisory institutions to strengthen risk-based control systems and protection for corruption whistleblowers.